Why digital skills are the new literacy? - Mohd Zaid, Noor Azila; Mohd Nasir, Hazira; Musa, Aini Hayati; Mohd Beta, Raja Mayang Delima; Idris, Asma’ Rashidah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Basic reading and writing skills are no longer sufficient in today's rapidly evolving digital world. A new form of literacy, referred to as digital literacy, is emerging. Digital literacy encompasses several key components, including technical skills, critical thinking and evaluation, communication and collaboration, as well as the safe and ethical use of technology. It is essential for successful participation in the digital society and is crucial for many users, particularly those in educational settings. Within the realm of education, digital literacy has attained paramount importance, spanning from primary education to higher education. It facilitates study, research, and professional growth by empowering students to proficiently utilise digital resources and tools (Cordell, 2013). Educational frameworks and curricula have been revised to incorporate digital literacy as an essential element.